Covid-19-Triggered Online Learning Implementation: Pre-Service English Teachers’ Beliefs - Adaninggar Septi Subekti (Metathesis: Journal of English Language, Literature, and Teaching, 2020)
The study investigated nine pre-service English teachers’ beliefs on the implementation of online learning due to the Covid-19 pandemic in their English Language Education Department. The study used secondary data in the forms of the participants’ written reflections on the implementation of online learning they experienced through their viewpoints both as students and as English teacher candidates. Qualitative document analysis in the form of Thematic Analysis was used to further analyse the data. The study found three factors hampering effective online learning, which were inadequate supporting infrastructures or resources, teachers’ limited pedagogical skills in effectively managing online learning, and the lack of teacher-student and student-student social connections during the learning process. The study also found two perceived good practices, the combination of synchronous and asynchronous modes, which could ease learners’ burden and boost learning effectiveness, and teachers' understanding of learners' struggle manifested in their facilitating actions. Based on the findings, the study's possible contributions and limitations are stated along with suggested directions for future studies in the field.